Membrane Organization of Bluetongue Virus Nonstructural Glycoprotein NS3 - Bansal, Om B. (American Society for Microbiology, 1998)
The smallest RNA segment (S10) of bluetongue virus (an orbivirus, family Reoviridae) encodes two closely related nonstructural proteins, the 229-amino-acid (aa) NS3 and the 216-aa NS3A. The proteins are found in glycosylated and nonglycosylated forms in infected cells (X. Wu, H. Iwata, S.-Y. Chen, R. W. Compans and P. Roy J. Virol. 66:7104–7112, 1992). The NS3/NS3A proteins have two hydrophobic domains (aa 118 to 141 and 162 to 182) and two potential asparagine-linked glycosylation sites (aa 63 and 150), one of which is located between the hydrophobic domains. To determine whether these features were used in the mature protein forms, we generated a series of mutants of the S10 gene and expressed them by using the vaccinia virus T7 polymerase transient-expression system. Our data indicate that both hydrophobic domains of NS3 span the cell membrane and that only the site at aa 150 is responsible for N-linked glycosylation of the NS3 proteins.